From podocyte biology to novel cures for glomerular disease - Torban, Elena; Braun, Fabian; Wanner, Nicola; Takano, Tomoko; Goodyer, Paul R; Lennon, Rachel; Ronco, Pierre; Cybulsky, Andrey V; Huber, Tobias B (Kidney international, 2019)
The podocyte is a key component of the glomerular filtration barrier. Podocyte dysfunction is central to the underlying pathophysiology of many common glomerular diseases, including diabetic nephropathy, glomerulonephritis and genetic forms of nephrotic syndrome. Collectively, these conditions affect millions of people worldwide, and account for the majority of kidney diseases requiring dialysis and transplantation. The 12th International Podocyte Conference was held in Montreal, Canada from May 30 to June 2, 2018. The primary aim of this conference was to bring together nephrologists, clinician scientists, basic scientists and their trainees from all over the world to present their research and to establish networks with the common goal of developing new therapies for glomerular diseases based on the latest advances in podocyte biology. This review briefly highlights recent advances made in understanding podocyte structure and metabolism, experimental systems in which to study podocytes and glomerular disease, disease mediators, genetic and immune origins of glomerulopathies, and the development of novel therapeutic agents to protect podocyte and glomerular injury.